PLANKTON AND HYDROLOGICAL FACTORS AT KANDLA IN THE GULF OF KUTCH DURING 1960—1963 - Dhawan, Rajinder M (Indian Journal of Fisheries, 2011)
The present studies relate mainly to the hydrological factors in the Gulf of Kutch at Kandlafrom August 1960 to December 1963. The seasonal variationin the temperature, salinity, pH, dissolved oxygen, inorganic phosphate, nitrite and silicate and their influence on plankton have been discussed. Temperature seems to be the only factor following the same pattern of variation during all the years. Dissolved phosphate and nitrite have a definite seasonal cycle among the nutrient salts. Fluctuation in salinity in the gulf appears to be erratic. Salinity and pH show a direct relationship in this area. The seasonal fluctuations of different plankters, both phytoplankton and zooplankton, have been discussed. The fluctuations in the phytoplankton count do not seem to be reflected on the total volume of plankton. It is seen that zooplankton content is mainly responsible for the variation in the plankton biomass